WHAT MAKES EDUCATION SO COMPLEX - Omarova, A.M.; Ashimkhanova, S.Z. (Халықаралық ғылыми форум МАТЕРИАЛДАРЫ 6–8 сəуір, 2016)
This article will attempt to answer on the question what makes education so complex in Kazakhstan. The issue will be examined in regard to two aspects economic priorities for the future and governmental policy, as these two concepts are more significant for a modern Kazakh society.
Keywords: концепт «образование»; система образования; трилингвизм; concept of education; education system; trilingualism